2015
DOI: 10.5018/economics-ejournal.ja.2015-38
|View full text |Cite
|
Sign up to set email alerts
|

Imported Inputs and Egyptian Exports: Exploring the Links

Abstract: This paper is the first to explore the links between exporting and importing activities of Egyptian firms using panel data over the period from 2003 to 2007. The main aim is twofold. Firstly, the authors report regression results indicating that firms that both export and import are the most productive, followed by importing-, exporting-only firms and non-traders. Secondly, they estimate the determinants of the extensive and intensive margins of exports and imports using dynamic panel-Probit and panel-Tobit mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The size of the firm is proxied with the number of employees in the firm, which follows The Indonesian Central Bureau of Statistics classifications. The correlation between size and export performances is expected to be positive (Edwards et al, 2018;Fan et al, 2015;Parra & Martínez-Zarzoso, 2015;Silva & Forte, 2018;Tomiura, 2007). Capital intensity is proxied as the firm's decomposed capital assets in machinery per labor.…”
Section: Methodsmentioning
confidence: 99%
“…The size of the firm is proxied with the number of employees in the firm, which follows The Indonesian Central Bureau of Statistics classifications. The correlation between size and export performances is expected to be positive (Edwards et al, 2018;Fan et al, 2015;Parra & Martínez-Zarzoso, 2015;Silva & Forte, 2018;Tomiura, 2007). Capital intensity is proxied as the firm's decomposed capital assets in machinery per labor.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, imported inputs ensure the production of high-quality varieties at a lower cost which boosts a firm's profits and makes the firm ready for the international market both in terms of the required quality and variety of the products. This has been documented and supported in the literature as the direct channel through which the importation of inputs enhances the probability of exporting (Bas and Strauss-Kahn, 2014;Feng et al, 2016;Edward et al, 2017;Grazzi et al, 2017;Castellani and Fassio, 2016;Kasahara and Lapham, 2013;Parra and Martínez-Zarzoso, 2015). Edwards et al (2017) and Feng et al (2016) emphasized the fact that it is imported inputs sourced from advanced economies that spur exporting activities and not imported inputs, in general.…”
Section: Empirical Findingsmentioning
confidence: 84%
“…Besides the preceding empirical discussion about the direct and indirect effects of imported inputs on firm export performance, there is equally a plethora of empirical literature examining the relationship between imported inputs and export performance of firms without explicitly stating the directness or indirectness of relationship (Edward et al, 2017;Bas and Strauss-Kahn, 2014;Feng et al, 2016;Castellani and Fassio, 2016;Pierola et al, 2015;Parra and Martínez-Zarzoso, 2015;Jienwatcharamongkhol, 2015;Grazzi et al, 2017;Turco and Maggioni, 2013;Muuls and Pisu, 2009;Kasahara and Lapham, 2013). For example, using manufacturing firm-level data from China, Feng et al (2016) showed that an increase in the importation of firm inputs is associated with an increase in exports and export product varieties with effects varying with the source of imports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation